2019
DOI: 10.1002/glia.23701
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning induces cortical microglial proliferation and a transcriptomic program of robust cell cycle activation

Abstract: Ischemic preconditioning (IPC) is an experimental phenomenon in which a subthreshold ischemic insult applied to the brain reduces damage caused by a subsequent more severe ischemic episode. Identifying key molecular and cellular mediators of IPC will provide critical information needed to develop novel therapies for stroke. Here we report that the transcriptomic response of acutely isolated preconditioned cortical microglia is dominated by marked upregulation of genes involved in cell cycle activation and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 77 publications
(195 reference statements)
15
39
0
Order By: Relevance
“…Among these genes, Mki67, Top2a, and Cenpf, which are cellular markers for proliferation, were increased in the MCAO model and decreased by EA treatment. This was consistent with previous RNA-seq reports of ischemic stroke (40,41). Previous studies also reported that following ischemic injury, the number of reactive astrocytes increased, and subsequently, microglia were activated since oxidative radical imbalance occurred (41).…”
Section: Discussionsupporting
confidence: 92%
“…Among these genes, Mki67, Top2a, and Cenpf, which are cellular markers for proliferation, were increased in the MCAO model and decreased by EA treatment. This was consistent with previous RNA-seq reports of ischemic stroke (40,41). Previous studies also reported that following ischemic injury, the number of reactive astrocytes increased, and subsequently, microglia were activated since oxidative radical imbalance occurred (41).…”
Section: Discussionsupporting
confidence: 92%
“… 78 Interestingly, IPC could induce cortical microglial proliferation dependent on fractalkine signaling. 79 RIPC inhibited inflammation by decreasing the levels of IL‐1β, IL‐6, and interferon‐γ in the ischemic brain. 80 Astrocytes are another type of glial cells which also exert immune regulation, 81 it mediate inflammatory effects by releasing neurotransmitters such as glutamate, and cytokines such as TNF‐α.…”
Section: Neuroprotective Mechanisms Of I/hpcmentioning
confidence: 94%
“…In addition, conditioned medium from HPC‐treated BMSCs could switch microglia toward anti‐inflammatory polarization and alleviate microglia‐induced injury by inhibiting the levels of pro‐inflammatory cytokines, such tumor necrosis factor (TNF)‐α, and upregulating anti‐inflammatory cytokines, such as IL‐10 78 . Interestingly, IPC could induce cortical microglial proliferation dependent on fractalkine signaling 79 . RIPC inhibited inflammation by decreasing the levels of IL‐1β, IL‐6, and interferon‐γ in the ischemic brain 80 .…”
Section: Neuroprotective Mechanisms Of I/hpcmentioning
confidence: 99%
“…While low-levels of proliferating microglia have been observed in the hippocampus of P301S mice , evidence shows that TIA1 regulates cell-cycle protein translation, with TIA1 reduction increasing cellular proliferation in vitro (Reyes et al, 2009;Sánchez-Jiménez and Izquierdo, 2015). Knockout of TIA1 in neural tissue has been shown to increase expression of CCNF and CDKN1 (Heck et al, 2014), cell cyclin proteins that are expressed during microglial proliferation after ischemic stroke (McDonough et al, 2020). Knockout of TIA1 may not only impact the inflammatory environment, contributing to microglial proliferation, but it may also increase expression of proteins integral for microglial proliferation.…”
Section: Tia1 Knockout Exacerbates Microgliosis In Advanced Tauopathymentioning
confidence: 99%